Penerapan Program Tahfidzul Qur’an Dan Problematikanya Di Madrasah Tsanawiyah Al Fathimiyah - Ratih Kusuma Ningtias (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The purpose of this research is to know 1) Application of the Program in MTs Al Fathimiyah 2) problems encountered in the Application of the program of tahfidzul Qur’an 3) Solutions to the problems that exist in the program of tahfidzul Qur’an. This research was conducted by the author using a qualitative approach with a Grounden Theory theoretical foundation that seeks to develop theories from the bottom / bases carried out by inductive ways to describe the implementation of the Tahfidzulqur'an program and its Problems at MTs Al Fathimiyah. The data collection method uses observation, interviews and documentation. There was also the first result in the Implementation of the Tahfidzul Qur'an Program in the Madrasah Tsanawiyah Al Fathimiyah, which went quite well by implementing the National Curriculum and the Qur'an Education Curriculum by emphasizing the addition of the subjects of Tahfidzul Qur'an, and supported by facilities to facilitate the Tahfidzul program. The Qur'an. In addition, the teachers in the Implementation of the Tahfidzul Qur'an Program are competent teachers in their field, especially in the material of the Tahfidzul Qur'an. Secondly, Problems encountered in implementing the Tahfidzul Qur'an Program include a) the difficulty of students achieving the targets that have been determined due to students difficulty in reading the Qur'an b) Lack of student awareness about the importance of memorizing the Qur'an and preserving it c) The existence of boredom from students when learning activities. Third, Madrasah Tsanawiyah Al Fathimiyah made an alternative solution to overcome the problematics of the Implementation of the Tahfidzul Qur’an Program